CORE-PLASMA-BANK PARTNERSHIPS IN THE PLANTATION SECTOR AFTER THE JOB CREATION LAW FROM THE PERSPECTIVE OF LEGAL CERTAINTY AND PROTECTION IN THE STATEWELFARE LAW - Yustinus Lambang Setyo Putro; Siti Nur Azizah; Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2026)
This research analyses legal certainty, legal protection, and tripartite legal responsibility in core–plasma–bank partnerships in the plantation sector after the enactment of the Job Creation Law. The reforms removed the explicit statutory obligation to provide 20% plasma smallholder area contained in the 2014 Plantation Law and shifted it into a regime of facilitation and private contracts, thereby increasing normative ambiguity and weakening the bargaining position of plasma farmers. Using a normative juridical method that combines statutory and conceptual analysis, comparative law, and case studies, the research finds that existing norms do not yet provide adequate guarantees for plasma farmers. In practice, tripartite arrangements often transfer credit risk to plasma farmers as direct debtors, while effective control over land, technology, and marketing remains with the core company and, through loan covenants, the Bank. The novelty of the dissertation lies, first, in demonstrating how the removal of the 20% obligation materially erodes smallholder protection, and second, in formulating the Equitable Tripartite Partnership Theory (TKTB), which positions the bank as a party to the partnership whenever financing is a constitutive element of the scheme. Comparative experience from Malaysia and the Philippines supports a more proportional role for banks through credit-guarantee schemes and contract oversight. The study recommends positivising TKTB in licensing, standard contracts, supervision, and credit-guarantee design so as to realise contractual justice and effective protection for plasma farmers in line with Pancasila and Article 33 of the 1945 Constitution.